2015
DOI: 10.1155/2015/835080
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequality in Cigarette Consumption, Cigarette Dependence, and Intention to Quit among Norwegian Smokers

Abstract: Background. The study aim was to examine the influence of education and income on multiple measures of risk of smoking continuation. Methods. Three logistic regression models were run on cigarette consumption, dependence, and intention to quit based on nationally representative samples (2007–2012) of approximately 1 200 current smokers aged 30–66 years in Norway. Results. The relative risk ratio for current versus never smokers was RRR 5.37, 95% CI [4.26–6.77] among individuals with low educational level versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
2
17
1
2
Order By: Relevance
“…Smoking attenuated educational inequality in breast feeding in both Norwegian and Dutch women. Smoking habits are socially patterned22 and consistently associated with shorter breastfeeding duration 6 8. This may be due to physiological factors such as decreased milk volume23 24 and altered sleep pattern,25 although behavioural factors seem to be most important 26…”
Section: Discussionmentioning
confidence: 99%
“…Smoking attenuated educational inequality in breast feeding in both Norwegian and Dutch women. Smoking habits are socially patterned22 and consistently associated with shorter breastfeeding duration 6 8. This may be due to physiological factors such as decreased milk volume23 24 and altered sleep pattern,25 although behavioural factors seem to be most important 26…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence on differences in quitting smoking by SES of tobacco users along different dimensions—such as, income, wealth, education, occupation, and residence in deprived areas—mostly pertains to high-income countries [1434]. These studies have consistently found that lower SES is predictive of lower probability of quit intention, quit attempts and successful quitting.…”
Section: Introductionmentioning
confidence: 99%
“…Smokers from the lower SES group also reported a lower intention to quit [27]. Recent research [2830] posited that the socialization of adolescents from lower income families of origin, such as the modelling or unhealthy lifestyles and health beliefs, could be transmitted intergenerationally to influence the adolescent’s smoking behavior. On the other hand, the uptake of EC and polytobacco use were highly associated with higher familial and personal income among smokers [22, 31].…”
Section: Introductionmentioning
confidence: 99%